2011
DOI: 10.1016/j.jcgg.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Living alone as a red flag sign of falls among older people in rural Taiwan

Abstract: a b s t r a c tBackground/Purpose: Fall is a common geriatric syndrome and is associated with physical injuries, fear of falling, limitation of activities of daily living, and increased medical expenditure. Although risk factors of falls have been explored extensively, little is known about the impact of solitary living on falls in the elderly. The main purpose of this study was to evaluate the impact of solitary living on risk of fall among older people who visited the outpatient geriatric services in rural T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Compared to pure‐tone audiometry, the gold standard for hearing loss assessment, self‐reported hearing loss has a sensitivity of 65%, a specificity of 85%, and a positive predictive value of 28% for bilateral hearing loss in a US‐representative sample . Neither audiometry nor self‐report has been more consistently associated with falls or fall‐related injury in the past . However, the self‐reported hearing‐loss measure we used herein has been associated with injuries in previous studies, and more strongly associated with self‐reported injury than pure‐tone audiometry in at least one study .…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Compared to pure‐tone audiometry, the gold standard for hearing loss assessment, self‐reported hearing loss has a sensitivity of 65%, a specificity of 85%, and a positive predictive value of 28% for bilateral hearing loss in a US‐representative sample . Neither audiometry nor self‐report has been more consistently associated with falls or fall‐related injury in the past . However, the self‐reported hearing‐loss measure we used herein has been associated with injuries in previous studies, and more strongly associated with self‐reported injury than pure‐tone audiometry in at least one study .…”
Section: Discussionmentioning
confidence: 85%
“…The NHIS sample is large, and because our analyses were weighted to reflect the age, sex, and race/ethnicity distribution of the 2010 Census, the association we observed between self‐reported hearing status and fall should be generalizable to the noninstitutionalized adult population of the United States. The 2016 NHIS included a supplemental section on dizziness and balance problems, permitting us to adjust for vestibular function, a major confounder that has not been consistently addressed in prior studies . While the subjectivity and nonspecificity of dizziness symptoms (eg, “a floating, spacey, or disconnected sensation”) can result in unreliable measurement of vestibular function in studies relying on self‐report, our definition of vestibular vertigo has a specificity of 94% and a sensitivity of 84% for clinically diagnosed vestibular vertigo and has been previously applied in several population‐based studies …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations